2010
DOI: 10.1007/s00439-010-0812-9
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of chronic venous disease

Abstract: Varicose veins without skin changes have a prevalence of approximately 20% in Northern and Western Europe whereas advanced chronic venous insufficiency affects about 3% of the population. Genetic risk factors are thought to play an important role in the aetiology of both these chronic venous diseases (CVD). We evaluated the relative genetic and environmental impact upon CVD risk by estimating the heritability of the disease in 4,033 nuclear families, comprising 16,434 individuals from all over Germany. Upon cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 20 publications
1
50
0
7
Order By: Relevance
“…CVI can affect the superficial venous system, the deep venous system, or both. Furthermore, the venous dysfunction may be the result of a congenital or acquired disorder [2][3][4] . Reflux-induced venous hypertension can be caused by breakdown or damage to the venous valves; more recently, it is believed that the lesion and weakness of the vessel wall play a more important role in causing reflux and even in the genesis of valve disease 1,5 -7 .…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
“…CVI can affect the superficial venous system, the deep venous system, or both. Furthermore, the venous dysfunction may be the result of a congenital or acquired disorder [2][3][4] . Reflux-induced venous hypertension can be caused by breakdown or damage to the venous valves; more recently, it is believed that the lesion and weakness of the vessel wall play a more important role in causing reflux and even in the genesis of valve disease 1,5 -7 .…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
“…Entre los factores de riesgo relacionados con esta patología se encuentran: La edad, el sexo femenino, historial familiar de venas varicosas, sedentarismo, obesidad, o antecedentes de trombosis venosa. También se asocian a la insuficiencia venosa factores medioambientales o de comportamiento como situaciones laborales que requieren que el sujeto esté prolongados periodos de tiempo de pie o sentado 5,6 . En las últimas décadas se ha realizado un esfuerzo por parte de los expertos para desarrollar una clasificación clínica bien establecida que siente las bases para un diagnóstico y tratamiento uniforme de la insuficiencia venosa crónica.…”
Section: Introductionunclassified
“…En las últimas décadas se ha realizado un esfuerzo por parte de los expertos para desarrollar una clasificación clínica bien establecida que siente las bases para un diagnóstico y tratamiento uniforme de la insuficiencia venosa crónica. Así en 1994, el informe de consenso del American Venous Forum presentó la Clasificación CEAP (Clínica, Etiológica, Anatómica y Patofisiológica) cuyos criterios se resumen en la tabla 1 3,6,7 . Para mayor información puede consultarse el documento de consenso y sus revisiones 8 .…”
Section: Introductionunclassified
“…Epidemiological studies have demonstrated that varicose veins have a definite hereditary nature of inheritance. 1,2 In conjunction with the presence of genes conferring disease susceptibility, various risk factors, such as prolonged standing, an increased body mass index, and preganancy, increases the mean venous pressure, in the lower extremities. 3,4 Pfisterer et al in 2014 found in an experimental mouse model that an escalated venous filling pressure induces varicose-like venous remodeling.…”
mentioning
confidence: 99%